Development and validation of a 3D-printed interfacial stress sensor for prosthetic applications. Issue 1 (January 2015) - Laszczak, P.; Jiang, L.; Bader, D.L.; Moser, D.; Zahedi, S.
<x xml:space="preserve">Abstract</x> Highlights 3D printed sensor for prosthetic applications is presented. The sensor is flexible and can simultaneously transduce pressure and shear. It exhibits high linearity (≈5–8%) and stress resolutions (≈0.6–1.3 kPa).